Comparison of specialised outpatient palliative care in heart failure and cancer patients: a German cross-sectional study - Johannes Maximilian Just; Klaus Weckbecker; Dennis Rottländer; Marie-Therese Schmitz; Ulrich Grabenhorst (BMJ Open)
Objectives Specialised outpatient palliative care (SOPC) is an important element of the palliative care concept in Germany. The aim of this study is to compare patient characteristics, care processes and outcomes of patients with heart failure (HF) and oncological diseases, using the latter as a reference group to identify disease-specific needs and support the adaptation of SOPC to non-oncological conditions such as HF.Design, setting and interventions In this cross-sectional study (22 SOPC providers), clinical data of all palliative care patients who were treated between 2017 and 2021 were retrospectively analysed.Primary and secondary outcome measures Survival was estimated by Kaplan-Meier analysis. To further examine the relationship between patient survival time and various variables, a Cox proportional hazards model was used. Differences in symptom burden were tested for statistical significance using the McNemar test.Participants Data from 48 882 patients were analysed, with 5387 (11.0%) identified as having a primary HF diagnosis. This cohort was compared against a large oncological group consisting of 34 287 (70.1%) patients.Results For HF patients, the mean number of days spent in SOPC was 30.5±67.7 days and for oncological patients 44.1±72.0 days. A significantly higher proportion of oncological patients died in hospices (14.0%) and hospitals (6.9%) compared with HF (2.9% and 2.2%). Age-adjusted Charlson Comorbidity Index at admission into SOPC was 9.4±3.1 in oncological patients compared with 6.7±1.7 in HF (p<0.001). The median survival time (ie, time spent in last treatment episode) for patients with HF was only 10 days, whereas patients with oncological diagnoses had a median survival of 24 days.Conclusions HF patients in SOPC exhibit a different clinical profile compared with oncological patients, characterised by significant symptom burden and shorter survival times. These results emphasise the necessity for tailored palliative interventions to address the specific needs of HF patients.